Advanced Functions for Signal Processing and Sensing Harnessing On-Chip SBS - Zarifi, Atiyeh; Stiller, Birgit; Eggleton, Benjamin J. (2018 IEEE 7th International Conference on Photonics, ICP 2018, 2018)
This paper reviews some of the significant SBSenabled signal processing applications in chalcogenide photonic waveguides and demonstrates a characterization technique to monitor the performance of this platform.
CRIS-Team Scopus Importer:2021-06-29
Keywords: BOCDA; Distributed SBS sensing; Photonic integrated waveguides; Stimulated Brillouin scattering(SBS); on-chip RF signal processing